EFFECTS OF POSTHARVEST HANDLING METHODS AND STORAGE CONDITIONS ON STORABILITY OF PEPPER (Capsicum frutescens L.) FRUITS IN SOUTHWEST NIGERIA (2014)
Pepper a perishable seasonal fruit, requires storage to extend its shelf-life. Appropriate postharvest handling and storage prolong longevity and preserve quality of Pepper Fruit (PF). However, there is dearth of information on its handling and storage in Southwest Nigeria. Therefore, the effects of postharvest handling methods and storage conditions on storability of PF were investigated. Two hundred Pepper Fruit Marketers (PFM) were randomly selected from pepper markets in Ibadan, Oyo State (Sasa and Bodija), Iwo, Osun state (Erunmu, Odo-Ori, and Station) and Akure, Ondo State (viz: Isikan, Oja-Oba, Sasa, NEPA and Isolo). Structured questionnaire was used to determine the socioeconomic characteristics of PFM and postharvest handling methods. Capsicum frutescens grown on the Teaching and Research Farm, University of Ibadan was harvested with and without pedicels at 10 and 100% ripeness. Postharvest handling was evaluated by comparing packaging in perforated polyethylene, non-perforated polyethylene and aluminium-foil before storing in either Ambient Conditions (AC) of 21.9-33.5°C and 58-62% Relative Humidity (RH); Refrigerator (4.0°C and 40-45% RH) or Evaporative Coolant Structure (ECS) (18 - 20°C and 70-75% RH). Pepper fruits were heat-sterilised, parboiled and unparboiled before oven-drying or sun-drying in order to determine the effect of processing on proximate and Vitamin C Content (VCC). Percentage Weight Loss (WL) was calculated. Firmness (FM) and Decay Level (DL) were evaluated on a scale of 1 to 4 and General Appearance (GA) on scale of 1 to 5. Data were analysed using descriptive statistics, correlation coefficient and ANOVA at p < 0.05. The average age of PF marketers was 45 years with male predominance (56%). Majority (69.0%) spread PF on cemented floor to minimise deterioration; Sixty-six percent removed spoilt fruits to reduce infection. Seventy-four percent sourced PF from middlemen these were inappropriately transported in commuter vehicles with used grain sack. Fruits were marketed at 100% ripeness without pedicels. Evidence of deterioration due to presence of insect larvae and rottenness was observed from the 5th day after storage. The shelf-life of PF harvested with pedicels at 10% ripeness and stored in refrigerator, ECS and AC was 27, 20 and 6 days, respectively, while shelf life of PF harvested at 100% ripeness was 21, 14, and 3 days, UNIVERSITY OF IBADAN LIBRARY iii respectively. In contrast, the shelf-life of PF harvested without pedicel at 10% ripeness was 21, 18 and 5 days while for 100% ripeness, it was 18, 15 and 2 days respectively. The WL, DL, GA and firmness of fruits harvested at 10% with pedicels and stored in refrigerator was 14.3%, 3.2, 4.0 and 3.5. The PF packaged in the aluminium-foil had significantly longer shelf life (30 days) than those packaged in perforated polyethylene (21 days) and non-perforated polyethylene (15 days). Parboiled-sundried pepper was significantly higher in crude protein (15.2%), fat (11.3 %), capsaicin (27.8%), and VCC (9.6 mg/100 g) compared to oven-dried pepper. Heat-sterilised fruits had the lowest nutrient contents. Storability of PF was best at 10% ripeness with pedicel. Parboiled-sundried method conserved nutrients better than other techniques. Keywords: Pepper storability, Postharvest handling, Capsicum frutescens. Word count: 487